Factors Influencing Running Velocity at Lactate Threshold in Male and Female Runners at Different Levels of Performance - Støa, Eva Maria; Helgerud, Jan; Rønnestad, Bent R.; Hansen, Joar; Ellefsen, Stian; Støren, Øyvind (Frontiers in Physiology, 2020)
Background The primary aim was to examine the relationship between lactate threshold (LT) expressed as percentage of maximal oxygen uptake (VO2max) and running velocity at LT (LTV). A secondary aim was to investigate to what extent VO2max, oxygen cost of running (CR), and maximal aerobic speed (MAS) determined LTV. A third aim was to investigate potential differences in LT and LTV between elite, national and recreational runners, as well as possible gender differences regarding VO2max, CR, LT, and LTV. Methods Seventy-five competitive runners (37 males and 38 females) with an average VO2max of 63.0 ± 9.3 mL⋅kg–1⋅min–1, and an average LTV of 13.6 ± 2.3 km⋅h–1 were tested for VO2max, LT, LTV, MAS, and CR. Results Lactate threshold did not correlate with LTV. With an r – value of 0.95 (p < 0.001) and a standard error of estimate of 4.0%, the product of MAS and individual LT determined 90% of LTV, outside a range of ±0.27 km⋅h–1. LTV increased with higher performance level. However, LT did not differ between elite, national and recreational runners. Female runners had 2.5% higher LT, 8% lower LTV, and 21% lower VO2max, but 9% better CR than male runners. Conclusion Lactate threshold did not correlate with LTV. The product of MAS and LT correlated strongly with LTV. There were no differences between elite, national and recreational runners regarding LT, but female runners had higher LT than the male runners. Female runners at the same relative performance level had lower LTV and VO2max, but better CR than male runners.